Investigation of JAM-A (rs790056) and LFA-1 (rs8058823) gene variants in Turkish colorectal cancer patients - Çaykara, Burcu; Alsaadoni, Hani; Hanım Pençe, Halime; Pençe, Sadrettin; Yılmaz Aydoğan, Hülya; Taştekin, Didem (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Lymphocyte function-associated antigen 1 (LFA-1) is a transmembrane glycoprotein expressed on the surface of leukocytes and containing the binding domain for junctional adhesion molecule-A (JAM-A). The aim of the present study was to evaluate the effects of JAM-A and LFA-1 variants on the formation of colorectal cancer and metastasis. Materials and Methods: A total of 82 subjects with colorectal cancer and 67 healthy subjects were studied. DNA was isolated from blood samples, and variations were determined using the polymerase chain reaction and restriction fragment length polymorphism method. Results: JAM-A rs790056 CC genotype and C allele were found to be higher in the colorectal cancer group (p<0.05), and approximately 3-fold increased colorectal cancer risk with CC genotype was determined (p=0.029). Haplotype analysis showed that GC haplotype (LFA-1 rs8058823G and JAM-A rs790056C) frequency was significantly higher in the patient group (p=0.041) than in controls. Conclusion: JAM-A rs790056 variation may be effective in the development of colorectal cancer.